RETRACTED: Shear Strength Behavior of Crude Oil Contaminated Sand-Concrete Interface - Amir Hossein Mohammadi; Taghi Ebadi; Mehrdad Ahmadi; Arash Aliasghar (Salehan Institute of Higher Education, 2016)
This article has been retracted: please see Civil Engineering Journal policies: (https://www.civilejournal.org/index.php/cej/about/editorialPolicies).This article has been retracted at the request of the Editor-in-Chief. It has come to our attention that there is significant duplication of text and content between this Civil Engineering Journal article and other paper by the same authors,